Electrochemical synthesis of a ternary transition metal sulfide nanosheets on nickel foam and energy storage application - Sahoo, Surjit; Naik, Kusha Kumar; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Alloys and Compounds, 2017)
We report growth of nickel cobalt sulfide (NCS) ultrathin nanosheets directly on Ni foam substrate by a facile and novel electrodeposition method. The as-prepared NCS sample is used as an electrode material for supercapacitor application due to their large electrochemically active surface area and interconnected nanosheet channels for the facilitation of ion transportation. The NCS nanosheets possess enhanced electrochemical performance in terms of fast and high reversible faradaic reactions characterized by prominent oxidation and reduction peaks. NCS nanosheets showed an ultrahigh specific capacitance of 1712 Fg(-1) at a current density of 1 Ag-1 with excellent cyclic stability. The excellent supercapacitor performance of NCS nanosheets can be attributed to its rich redox reactions as well as high transport rate for both electrolyte ions and electrons. (C) 2016 Elsevier B.V. All rights reserved.